Characterization of the virulence, growth temperature and antibiotic resistance of the Campylobacter jejuni IAL 2383 strain isolated from humans - Fonseca,B.B. (2014)
The objective of this study was to characterize the C. jejuni IAL2383 strain isolated from humans in Brazil. Transcripts for the racR, dnaJ and ciaB genes were found and flaA, plda and cadF genes were present in the genome and bacteria was sensitive to most of the important antimicrobials used to treat humans. C. jejuni IAL2383 is a good experimental model to analyze the interactions with cells.